Analisis Framing Pemberitaan Online Gerakan Indonesia Tanpa Feminis - A’yun Masfupah (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2019)
Some time ago an Instagram account called Indonesia without feminists appeared, this account was created as a medium to spread the news that there was a group of people who wanted to eliminate feminism in Indonesia. They say that Indonesia does not need a feminist movement to defend women's rights because even in Islam women have been glorified. Although the Indonesian movement without feminists reaps a lot of responses from both positive and negative people researchers only found a few online news sites that discussed the news, this news was first raised by The Jakarta Post on April 1, 2019 with the headline